2000
DOI: 10.1016/s0928-8244(00)00167-x
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiological activities of a chemically synthesized lipid A of Porphyromonas gingivalis

Abstract: A synthetic lipid A of Porphyromonas gingivalis strain 381 (compound PG-381), which is similar to its natural lipid A, demonstrated no or very low endotoxic activities as compared to Escherichia coli-type synthetic lipid A (compound 506). On the other hand, compound PG-381 had stronger hemagglutinating activities on rabbit erythrocytes than compound 506. Compound PG-381 also induced mitogenic responses in spleen cells from lipopolysaccharide (LPS)-hyporesponsive C3H/HeJ mice, as well as LPS-responsive C3H/HeN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 26 publications
0
33
1
Order By: Relevance
“…Although our present results strongly indicated that LPS from P. gingivalis and C. ochracea are antagonists for human TLR4, it has been reported that a synthetic lipid A of P. gingivalis activated C3H/HeN macrophages but not C3H/ HeJ macrophages, indicating that mouse TLR4 played an essential role in the response to this compound (24). To address the question of whether the antagonistic activities of LPS from P. gingivalis and C. ochracea are species specific, CHO/CD14 cells which express a functional hamster TLR4 transcript were transfected with human TLR4.…”
Section: Fig 5 Lps From P Gingivalis and C Ochracea Blocked The Scontrasting
confidence: 77%
“…Although our present results strongly indicated that LPS from P. gingivalis and C. ochracea are antagonists for human TLR4, it has been reported that a synthetic lipid A of P. gingivalis activated C3H/HeN macrophages but not C3H/ HeJ macrophages, indicating that mouse TLR4 played an essential role in the response to this compound (24). To address the question of whether the antagonistic activities of LPS from P. gingivalis and C. ochracea are species specific, CHO/CD14 cells which express a functional hamster TLR4 transcript were transfected with human TLR4.…”
Section: Fig 5 Lps From P Gingivalis and C Ochracea Blocked The Scontrasting
confidence: 77%
“…2), and LPS-PW exhibited the properties of both PGP and LPS-PCP in murine cells (12), suggesting that the unique bioactivities of LPS preparations of BPB and related bacteria reported to date are derived from some PGPlike molecule(s). In support of this possibility, a chemically synthesized P. gingivalis lipid A activated macrophages to produce IL-6 and TNF-␣ from C3H/HeN mice but not from C3H/ HeJ mice (25).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, the observed activities of P. gingivalis LPS might be attributable to PGP or PGP-like material possibly present in the LPS fraction. In this context, previous research has shown that a synthetic compound mimicking P. gingivalis lipid A, unlike the natural counterpart, did not activate macrophages from C3H/HeJ mice [20].…”
Section: Mrna Expression For Il-8 G-csf Gm-csf and Icam-1 By Gingivmentioning
confidence: 91%